2018
DOI: 10.1007/s11356-018-3975-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electronic cigarette vaping on the composition of indoor organic pollutants, particles, and exhaled breath of bystanders

Abstract: The changes of particles and organic pollutants in indoor atmospheres as consequence of vaping with electronic cigarettes have been analyzed. Changes in the composition of volatile organic compounds (VOCs) in exhaled breath of non-smoking volunteers present in the vaping environments have also been studied. The exposure experiments involved non-vaping (n = 5) and vaping (n = 5) volunteers staying 12 h together in a room (54 m 2) without external ventilation. The same experiment was repeated without vaping for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…E‐cigarette use increases indoor PM 2.5 concentration, as shown by a significantly higher concentration during e‐cigarette use (vs. pre‐exposure) at both near‐ and far‐field exposure. This trend was in line with previous experimental studies which showed an increase in PM 2.5 concentration during puffing period to a mean concentration level that ranged from 20 to 290 μg/m 3 9–11 . In an extreme situation, a study conducted during an e‐cigarette convention found that the concentration of PM 2.5 was able to reach as high as 819 µg/m 3 , 12 levels that are higher than in hookah cafes and bars that allow smoking inside 47 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…E‐cigarette use increases indoor PM 2.5 concentration, as shown by a significantly higher concentration during e‐cigarette use (vs. pre‐exposure) at both near‐ and far‐field exposure. This trend was in line with previous experimental studies which showed an increase in PM 2.5 concentration during puffing period to a mean concentration level that ranged from 20 to 290 μg/m 3 9–11 . In an extreme situation, a study conducted during an e‐cigarette convention found that the concentration of PM 2.5 was able to reach as high as 819 µg/m 3 , 12 levels that are higher than in hookah cafes and bars that allow smoking inside 47 .…”
Section: Discussionsupporting
confidence: 91%
“…Unlike the present study, previous experiments showed an increased concentration of airborne nicotine during e‐cigarette use period. However, these studies had longer periods of e‐cigarette use, from 2 to 12 hours, involved more than one user at a time, and did not employ ad libitum use 9,10,40 . The unquantifiable concentration of airborne nicotine in this study may be because the method only captured the nicotine in the gas phase, not particle phase, thus, underestimating the chemicals present 50 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Airborne particles with an aerodynamic diameter lower than 2.5 µm (PM 2.5 ) are mainly constituted of carbonaceous materials, including elemental carbon (EC) and organic carbon (OC) [1,2] and contain thousands of organic compounds that contribute to their toxic potential [3][4][5]. Combustion by-products generated during fossil fuel or biomass burning are responsible for a significant fraction of these toxic compounds, such as polycyclic aromatic hydrocarbons (PAHs) [6][7][8] which may be found both in outdoor and indoor atmospheres [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Since e-cigs do not burn tobacco, vaping is not associated with the inhalation of combustion products. The analytical studies currently available show that at normal usage of the products the harmful constituents of tobacco smoke are either absent or present only in trace amounts in the inhaled aerosol [2, 3] and in the air of closed rooms after vaping [4, 5]. Some researchers described e-cig vapor as being similarly harmful as tobacco smoke because of the emission of particulate matter without considering the difference between the harmful solid particles in smoke and benign liquid droplets in e-cig aerosols [6].…”
Section: Introductionmentioning
confidence: 99%